Peran Guru dalam Membangun Kepercayaan Diri Siswa melalui Pembelajaran Aktif di Kelas Dasar - Anisa Masyitoh; Cindy Aulia Safmi; Gusmaneli (Journal Educational Research and Development | E-ISSN : 3063-9158, 2024)
This study examines the impact of active learning on students' self-confidence, academic performance, and social skills. The primary objective is to understand how active learning approaches, such as group discussions, problem-solving activities, and collaborative projects, influence students' belief in their abilities and overall academic success. The research employs a qualitative approach, gathering data from classroom observations and student interviews to assess changes in behavior and performance. Findings suggest that students with high self-confidence demonstrate increased motivation, better academic achievement, and improved social interactions. Active learning encourages participation, critical thinking, and teamwork, which enhances both academic outcomes and social competence. Despite challenges, such as student resistance and time constraints, strategies like creating a supportive environment and providing positive reinforcement can foster a successful active learning experience. The study concludes that active learning plays a significant role in developing self-confidence and improving academic and social outcomes in students.